The effect of market access on the labor market: Evidence from German reunification - Ulrich Zierahn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The New Economic Geography predicts a positive effect of market access on wages, as represented by the wage equation. Several studies provide empirical evidence in favor of the wage equation. However, a key problem is the endogeneity of market access: it is challenging to identify the causal effects of market access on wages, since market access itself depends on wages. Whereas most approaches rely on instrumental variables and strong assumptions on exogeneity, the present analysis relies on German reunification as an exogenous variation of market access in order to identify the effects. Since the market access shock due to reunification was accompanied by a labor supply shock due to migrants and commuters from eastern Germany, the effects on wages, employment and unemployment are analyzed. The results provide evidence in favor of a labor demand shock due to the increase in market access and a labor supply shock due to migrants and commuters from eastern Germany.
Keywords: F15; R12; R23; 330; New Economic Geography; wage equation; market access; natural experiment; differences-in-differences; Lohnkurve; Markteintritt; Neue Ökonomische Geographie; Nationale Einheit; Schock; Deutschland